ANALISIS KINERJA BPS DALAM PENYUSUNAN PDRB MELALUI SURVEI NERWILIS DI KOTA SEMARANG - Adi Nugroho; Hardi Warsono; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Performance is a parameter by which the extent of implementation of particular activity/program/policy can be achieved in order to obtain particular target, objective, vision, and mission of an organization, which has been predetermined in the organizational planning strategy. Performance can be assessed and measured if individuals or group of individuals have already had criteria or standard by which a successful work can be achieved. Therefore, organizational success cannot be obtained without clear target and objective. This study applied a public administration and five performance indicators, i.e. productivity, service quality, responsiveness, responsibility, and accountability. The study performed a descriptive, qualitative method to expose the findings from the field observation. Data were collected by means of interview, observation, and documentation, involving key informants from the Semarang Municipal Office of the Center for Statistic Bureau as well as concerned stakeholders. The study resulted in as the followings: poor performance of the Center for Statistic Bureau in developing the Gross Regional Income report as it might be evidenced from the Nerwilis survey. There were still lacking productivity, poor data quality, and inadequate human resources. However, the Semarang Municipal Office of the Center for Statistic Bureau had been supported by good organizational vision and mission, staff competency, experience, and technological advance. All of these aspects helped the Center to present the data required by the governmental institutions as well as the stakeholders. In other words, performance transparency had been achieved. This study recommended an incidental field staff recruit and socialization of the importance of the statistics in the modern era.